From the Transit of the Sierra to the Coast. Report of sites in Quebrada Cruz de Hueso - Bautista Cornejo, Edgar David (2007)
This paper presents field data of a survey into the Cruz de Hueso Basin. This survey was based on my interest for a more thorough knowledge of the potential of the archaeological sites that were located within the basin, between its point of origin and the point known as Capilla de Chamaure. Another factor that motivated us to make this survey was the importance of the basin as traffic road and connection toward the highlands of Huarochirí and from there toward the coast, becoming this way the complement or control of sea and height resources, for the ancient societies that were developed in this area. Also, we present the data that we were able to gather from the archaeological site of Caringa, with the aim of approaching to the subsistence of the human group that lived in a seasonal ecosystem as the lomas of southern Lima, besides providing some data on their social organization.